Scholarly communication in open science: A study of cognitive, conative and affective readiness of researchers in Malaysia / Wusu, Oluwaseyi Hodonu - Wusu, Oluwaseyi, Hodonu (2021)
The study aims to investigate the readiness of Malaysian academic researchers’ open scholarly communication focusing on the three most important pillars of Open Science i.e., Open Access, Open Data and Open Peer Review. The study answered the extent of Malaysian academic researchers’ cognitive, conative, and affective readiness as regards to Open Access, Open Data and Open Peer Review, as well as finding out significant differences between gender, types of researchers, and research discipline. A survey instrument of 75 questions about open scholarly communication was sent to academic researchers in five research universities in Malaysia between February and August 2018. A total of 135 responses from the questionnaire were analyzed via simple percentage. The sample size was determined as 370 (confidence level=95%, margin of error=2.5%) however, oversampling was carried out to be 400 from a population of 9,299. A total of 135 were returned for a response rate of 33.75%. The results showed the researchers’ cognitive, conative, and affective readiness of Open Access, Open Data and Open Peer Review. From the study, it was revealed Malaysian researchers are generally aware of Open Access; but have low levels of awareness of Open Data and Open Peer Review. Practices of open scholarly communication are still low as reflected in the mean scores, especially on open data sharing and open peer reviewing, probably because they do not want to be associated with bad comments syndrome in science, as well as the fear of losing publication rights. Lack of incentives and misuse of data are part of disincentives for data sharing. It is widely believed that Open Peer Review will ensure transparent, provide honest feedback, increased motivation and improve science, but the issue of timing in reviewing and fear of negative comments are concerns to many respondents. The study concludes in terms of readiness that Malaysian academic scholars are somewhat ready and grouped as strollers, they are moving ahead with the trend of open scholarly communication. Future studies should investigate the importance or rewards for openness, especially in data sharing among scholars’ institutions, and studies bridging the gap between policy and practices of open science should be examined.